2014
DOI: 10.5455/medarh.2014.68.54-56
|View full text |Cite
|
Sign up to set email alerts
|

External Dacryocystorhinostomy with and Without Suturing the Posterior Mucosal Flaps

Abstract: Purpose:To evaluate the outcome of the external dacryocystorhinostomy with and without suturing the posterior mucosal flaps.Methods:This study included 106 patients with lacrimal drainage system disorders who underwent the external dacryocystorhinostomy. Fifty four patients (Group A) underwent external dacryocystorhinostomy with suturing anterior and posterior flaps of the lacrimal sac and nasal mucosa, and the results obtained were compared with those of another series of 52 patients (Group B) where dacryocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
4
10
0
7
Order By: Relevance
“…On the contrary to this assump on, there was no significant associa on between type of flap anastomosis with the outcome of the surgery in our study, which is similar to the study conducted by Turkcu, Elwan 26,27,28 a n d . W h i l e p e r f o r m i n g e x t e r n a l K a c a n i k u dacryocystorhinostomy surgery, anastomosis of both the flap is technically difficult and me consuming compared to the anastomosis of anterior flap only.…”
Section: Original Research Articlesupporting
confidence: 82%
“…On the contrary to this assump on, there was no significant associa on between type of flap anastomosis with the outcome of the surgery in our study, which is similar to the study conducted by Turkcu, Elwan 26,27,28 a n d . W h i l e p e r f o r m i n g e x t e r n a l K a c a n i k u dacryocystorhinostomy surgery, anastomosis of both the flap is technically difficult and me consuming compared to the anastomosis of anterior flap only.…”
Section: Original Research Articlesupporting
confidence: 82%
“…[2][3][4] Although double-flap anastomosis is technically difficult and time-consuming, it has been a key procedure in achieving higher success of ex-DCR. [2][3][4][5][6] The success rate of ex-DCR without mucosal flap anastomosis (88.0%-97.9%) is reportedly similar to that of the double-flap anastomosis technique, 2,3,5 -18 resulting in some doubt regarding the usefulness of mucosal anastomosis in obtaining a higher success rate of ex-DCR.…”
supporting
confidence: 51%
“…For comparison, numerous studies have reported the success rate for external DCR to 90%‐98% (Delaney & Khooshabeh ; Tsirbas et al. ; Kacaniku & Begolli ; Caglar et al. ; Lee et al.…”
Section: Discussionmentioning
confidence: 99%